ANALISIS ANOMALI PASAR JANUARY EFFECT PADA SAHAM PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA - Fachry Banan (2022)
This research aims to examine the differences in the January Effect market anomaly on the shares of coal sub-sector companies listed on the Indonesia Stock Exchange. This market anomaly phenomenon is an abnormal increase in prices every January, called January Effect. The variables selected in this study are stock returns, abnormal returns, and Trading Volume Activity. The sample taken is 21 coal companies on the Indonesia Stock Exchange. The sampling method is by selecting active coal companies that were not delisted in the 2017-2021 period. The hypothesis tests are the independent sample t-test and the Mann-Whitney test. The results of this research state that there is no January effect phenomenon and no difference in abnormal returns and Trading Volume Activity, but for the stock return variable, there is a difference compared to the other eleven months in the shares of coal companies on the Indonesia Stock Exchange.